Activation of C–H bonds by rare-earth metallocene-butyl complexes. Issue 72 (23rd August 2017) - Grindell, Richard; Day, Benjamin M.; Guo, Fu-Sheng; Pugh, Thomas; Layfield, Richard A.
Abstract : The stable metallocene-butyl complexes [(Cp Me )2 M( n Bu)]2 (M = Y, Dy) were synthesized and their reactivity towards to ferrocene and bulky N-heterocyclic carbenes investigated. Abstract : The stable metallocene-butyl complexes [(Cp Me )2 M( n Bu)]2 (M = Y, Dy) were synthesized and their reactivity towards to ferrocene and bulky N-heterocyclic carbenes investigated. Selective mono-deprotonation of ferrocene and a benzylic methyl group of IMes were observed, whereas a control reaction of (Cp Me )3 M with IMes resulted in a normal-to-abnormal NHC rearrangement.